Evaluation of a sprinkle irrigation system with the use of a frequency inverter drive - de Araújo, João Alberto Borges; Seraphim, Odivaldo José [UNESP]; Siqueira, Jair Antonio Cruz; Presenço, Fernando [UNESP]; Caneppele, Fernando de Lima [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2006)
This work aimed to evaluate the use of a frequency inverter drive on the electric and hydraulic parameters of a sprinkling irrigation śystem management. A conventional sprinkle water pump system with 4 alternate controlled lines, in which the opening of 1, 2, 3 and 4 lines occurred simultaneously; electric energy consumption and hydraulic parameters of the system were registered. Later on, this system was connected to a starting system with varied rotation, consisting of a pressure transducer and a frequency inverter drive, that made the water pump rotation vary and adapted the preset pressure in relation to f the flow variation requested by the system. Obtained results showed that, in the system with a frequency inverter drive, there was reduction of the electric energy consumption and the service pressure of the sprinkling was maintained, just varying the requested flow, for the simultaneous management of 1, 2 and 3 lines.
Avaliação de um sistema irrigação por aspersão com aplicação do inversor de freqüência no conjunto motobomba
Keywords: Energy consumption; Hydraulic parameters; Irrigation management